2021
DOI: 10.3389/fcell.2021.685873
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Fluid Stem Cell-Derived Exosomes as a Novel Cell-Free Therapy for Cutaneous Regeneration

Abstract: Adult wound healing often results in fibrotic scarring that is caused by myofibroblast aggregation. Human amniotic fluid stem cells (hAFSCs) exhibit significantly anti-fibrotic scarring properties during wound healing. However, it is little known whether hAFSCs directly or indirectly (paracrine) contribute to this process. Using the full-thickness skin-wounded rats, we investigated the therapeutic potential of hAFSC-derived exosomes (hAFSC-exo). Our results showed that hAFSC-exo accelerated the wound healing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…This can be easily obtained by either incubating cells in xeno- and serum-free medium (SF) formulations or by employing commercially available or home-made FBS-EV-free supplements. Most studies focusing on hAFSC-EVs apply SF culture conditions [ 19 , 46 , 47 , 54 , 57 , 58 , 60 , 67 , 84 , 87 , 89 ], while fewer groups have reported using EV-free culture medium to collect the cell-CM [ 55 , 56 ]. Likewise, other variables have been shown to prime stem cell and MSC secretory potential, such as oxygen tension or pro-inflammatory stimuli (i.e., IFNγ) [ 84 ].…”
Section: From the Bench To The Bedside: Translating Promising Results Over Methodological Concernsmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be easily obtained by either incubating cells in xeno- and serum-free medium (SF) formulations or by employing commercially available or home-made FBS-EV-free supplements. Most studies focusing on hAFSC-EVs apply SF culture conditions [ 19 , 46 , 47 , 54 , 57 , 58 , 60 , 67 , 84 , 87 , 89 ], while fewer groups have reported using EV-free culture medium to collect the cell-CM [ 55 , 56 ]. Likewise, other variables have been shown to prime stem cell and MSC secretory potential, such as oxygen tension or pro-inflammatory stimuli (i.e., IFNγ) [ 84 ].…”
Section: From the Bench To The Bedside: Translating Promising Results Over Methodological Concernsmentioning
confidence: 99%
“…Indeed, several groups reported that in vitro hypoxic preconditioning may lead to an increased secretome yield, including EV fractions [ 47 , 54 , 89 ]. The duration of preconditioning is another sensible aspect, since hAF-MSC/hAFSC-CM has been reported to be collected after 24 h [ 46 , 47 , 67 , 89 ], 48 h [ 19 , 60 ], 72 h [ 56 ] or 96 h [ 57 , 58 ]. Notably, hAF-MSC and hAFSC have been suggested to mature different miRNA profiles which can be further enriched in their EV cargo, depending on culture conditions [ 54 ].…”
Section: From the Bench To The Bedside: Translating Promising Results Over Methodological Concernsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes secrete from T cells ( Nolte-‘t Hoen et al, 2009 ), B cells ( Clayton et al, 2005 ), macrophages ( Bhatnagar et al, 2007 ), epithelial cells ( Skogberg et al, 2015 ), endothelial cells ( Song et al, 2014 , 2015 ), as well as MSCs ( Yeo et al, 2013 ). The vesicles with exosomal characteristics have been also founded in the various body fluids such as semen ( Fabiani et al, 1994 ; Arienti et al, 1999 ; Park et al, 2011 ; Aalberts et al, 2012 ), blood ( Blanc et al, 2005 ; Caby et al, 2005 ; Yunusova et al, 2016 ), breast milk ( Admyre et al, 2007 ; Qin et al, 2016 ; Miyake et al, 2020 ), ascites fluid ( Andre et al, 2002 ; Navabi et al, 2005 ; Runz et al, 2007 ), saliva ( Ogawa et al, 2008 ; Michael et al, 2010 ), amniotic fluid ( Asea et al, 2008 ; Zhang et al, 2021 ), urine ( Gonzales et al, 2010 ; Street et al, 2017 ), and bile ( Masyuk et al, 2010 ; Sagredo et al, 2017 ). Because exosomes are in nano sized range, they spread through body fluids and easily penetrate through tissues and affect targeted cells ( Phinney and Pittenger, 2017 ), even if those cells are far away ( François et al, 2006 ).…”
Section: Exosome: General Aspectsmentioning
confidence: 99%